Pengaruh Motivasi, Disiplin Kerja dan Kepemimpinan terhadap Kinerja Karyawan Coffee Shop di Kota Batam - Setiawan, Kendri; Sentoso, Antony (Universitas Islam Kadiri, 2024)
The purpose of the study was to determine the effect of motivation, work discipline and leadership on the performance of Coffee Shop employees in Batam City. Employee performance is very much needed by a coffee shop to improve operational efficiency so that it can maximize profits. The research method used is quantitative, the technique in data collection uses sampling techniques by distributing questionnaires with a sample of 250 respondents. Data analysis techniques use SPSS. 25 with several tests. The results of the study indicate that there is a significant effect of motivation on employee performance, there is a significant effect of work discipline on employee performance and a significant effect of leadership on employee performance.